Inverse Compton X-rays from Giant Radio Galaxies at z~1 - Laskar, T; Fabian, A; Blundell, K; Erlund, M (2009)
We report XMM-Newton observations of three FR II radio galaxies at redshifts between 0.85 and 1.34, which show extended diffuse X-ray emission within the radio lobes, likely due to inverse-Compton up-scattering of the cosmic microwave background. Under this assumption, through spectrum-fitting together with archival VLA radio observations, we derive an independent estimate of the magnetic field in the radio lobes of 3C 469.1 and compare it with the equipartition value. We find concordance between these two estimates as long as the turnover in the energy distribution of the particles occurs at a Lorentz factor in excess of ~ 250. We determine the total energy in relativistic particles in the radio emitting lobes of all three sources to range between 3e59 and 8e59 erg. The nuclei of these X-ray sources are heavily-absorbed powerful AGN.